Methylprednisolone for Prevention of Seroma Formation after Mastectomy - Danyal Anwar Shiraz, Maham Qazi, Irum Sabir, M Khurram Jameel, Ch. Muhammad Aqeel, Mah Muneer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer is the most common cause of death in middle aged women. Seroma formation is claimed to be a very common problem after axillary dissection in patients with breast cancer. Aim: To conduct this study to see if injecting methyl prednisolone can improve the post-operative outcomes of modified radical mastectomy in terms of seroma formation Methods: This Study design is a randomized control trial, done at Surgical Department, Khyber Teaching Hospital, Peshawar from October 12th 2019 till April 12th 2020. Randomization was done through lottery method. Sample size was 38 in each group. All the data was analyzed in SPSS (version 22). Mean + SD was calculated for continuous variables like age, BMI and volume of seroma. Frequency and percentages were calculated for categorical variables like stage of breast cancer, whether neoadjuvant chemotherapy was received andefficacy. Efficacy in both groups was compared using chi square test keeping p value of <0.05 as significant. Result: Mean age in Group A was 38±12.72 years whereas in Group B was 40±11.83 years. Efficacy of both the groups was analyzed as Group A ( Methyl prednisolone) was effective in 76% patients in preventing seroma formation. Normal Saline injection in Group B was effective in preventing seroma formation in 53% patients. Methylprednisolone being statistically significant in prevention of seroma formation with a p value of 0.03. Conclusion: Our study concludes that local methyl prednisolone is more effective than normal saline injection in preventing seroma formation after modified radical mastectomy for carcinoma breast. Clinical Implications: This study will not only add to the national and international literature that is available on the topic but would also help us in modifying in treatment guidelines if proven efficacious in order to improve patient management. Keywords: Breast Cancer, Methylprednicolone, modified radical mastectomy, seroma, normal saline